2 YEARS AFTER MERGERS: SERVICE QUALITY, CUSTOMER SATISFACTION, AND CUSTOMER LOYALTY BANK SYARIAH INDONESIA CUSTOMERS - Bayhaqy Mochamad; Fitrisia Septiarini Dina (Universitas Airlangga, 2023)
After going through the transition period until the second year, Bank Syariah Indonesia has some tasks to be carried out after mergers with three established sharia banks that have different sectors and backgrounds of customers, making it somewhat challenging for Bank Syariah Indonesia to maintain service quality, satisfaction, and loyalty from customers of the three previous banks. This study is quantitative research; data from distributed questionnaires online to Bank Syariah Indonesia customers that have used Bank Mandiri Syariah, Bank BRI Syariah, and Bank BNI Syariah and have used Bank Syariah Indonesia for two years yielded 206 answers. The data analysis technique is SEM PLS with SmartPLS 4.0. From this study, we find a significant relationship between Service Quality with Customer Loyalty, Customer Satifaction with Customer Loyalty, Service Quality with Customer Satisfaction, and Service Quality with Customer Loyalty through the intervention of Customer Satisfaction. concluded that customers agree that they are still receiving service quality and satisfaction with Bank Syariah Indonesia compared with three previous banks and agree that they will give their loyalty to Bank Syariah Indonesia. Keywords: Mergers, Bank Syariah Indonesia, Service Quality, Customer Satisfaction, Customer Loyalty.